Implementation of the Socratic Question Learning Model in Developing Critical Thinking Skills of Grade XI Students in Fiqh Learning at Madrasah Aliyah Hidayatul Mubtadiin South Lampung - Faturrahman Faturrahman; Etika Pujianti; Nur Widiastuti (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to describe the implementation of the Socratic Question Learning Model in developing critical thinking skills of grade XI students in Fiqh learning at Madrasah Aliyah Hidayatul Mubtadiin, and to identify supporting and inhibiting factors in its implementation. The research method used is a qualitative approach with a descriptive research type. Data collection techniques include observation, in-depth interviews, and documentation, while data validity is obtained through triangulation of sources and techniques. The results of the study indicate that the implementation of the Socratic Question Learning Model is able to improve students' critical thinking skills, which is characterized by increased ability to analyze Fiqh law, compile logical arguments, contextualize Islamic law with contemporary issues, and internalize tabayyun attitudes and intellectual humility. The main supporting factors include Islamic boarding school culture (bahtsul masail), managerial policy support, and the availability of learning resources, while inhibiting factors include time constraints, differences in students' verbal abilities, and the influence of digital instant culture. This study concludes that the Socratic Question Learning Model is effective for use as a Fiqh learning strategy to develop students' critical thinking skills comprehensively and sustainably